Navigating Complexity: The Dynamics of Organisational Culture during a Merger - Dayaram, Kandy (School of Management, Curtin University of Technology, Perth, Western Australia and the Singapore Human Resources Institute, 2005)
Despite enthusiasm for the South African Constitutional obligation of 1996 to redress inequities in the public education sector, the integration of previously advantaged and disadvantaged colleges has realised enormous challenges and the progress has been slow. Many of these challenges are manifested in values, attitudes and behaviours which are rooted in traditional cultural baggage. This paper will focus on the dilemmas and enigmas encountered by participants in education contexts that are undergoing sea change in mindsets and work practices. Specifically, this paper employs a case study to delineate the major challenges that arise when contemporary transformational initiatives clash with traditional rigid and inflexible college cultures. The implications for human resource management (HRM) practices and policies in public sector institutions contemplating similar revitalisation are discussed.